Functional residual capacity related to hepatic disease. Issue 7 (July 1988) - Greenough, A; Pool, J; Ball, C; Mieli-Vergani, G; Mowat, A
Abstract : Functional residual capacity was measured in 20 children (aged 3.1-11.2 years) with liver disease. Children with severe liver disease, regardless of diagnosis, had reduced functional residual capacities (less than 80% of expected). Children with alpha-1 antitrypsin deficiency had higher functional residual capacities than those with other hepatic diagnoses. Three children had a functional residual capacity greater than 120% of expected, all had alpha-1 antitrypsin deficiency.